Flexible devices fabricated by a plate-to-roll nanoimprint lithography system. (14th December 2018) - Xu, Kai; Luo, Huiwen; Qin, Jin; Yang, Muyi; Guo, Songpo; Wang, Liang
Abstract: A plate-to-roll nanoimprint lithography (P2RNIL) system has been developed to realize a high-speed, large-scale and high-resolution nanoimprint process. Imprinted patterns have been achieved with a linewidth of less than 75 nm at a speed of 22 cm 2 s −1 on flexible substrate. To improve the quality of the imprinted patterns, we have proposed a compliant mechanism which can realize passive alignment and minimize the lateral displacement between template and substrate. Finite element analysis of this compliant mechanism was carried out. By using the P2RNIL system, wire-grid polarizers (up to a 10 030:1 extinction ratio and up to 88% transmittance) and transparent metal electrodes whose performance is in good accordance with simulated results were successfully fabricated.